2013
DOI: 10.1155/2013/359621
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Reagents Mimicking Oxidative Stress on Fibrinogen Function

Abstract: Fibrinogen is one of the plasma proteins most susceptible to oxidative modification. It has been suggested that modification of fibrinogen may cause thrombotic/bleeding complications associated with many pathophysiological states of organism. We exposed fibrinogen molecules to three different modification reagents—malondialdehyde, sodium hypochlorite, and peroxynitrite—that are presented to various degrees in different stages of oxidative stress. We studied the changes in fibrin network formation and platelet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 44 publications
3
34
0
2
Order By: Relevance
“…It is believed that this in vitro system provides a sufficient correlation with the in vivo oxidative stress. 20,36 The hypochlorite concentration used in this study is somewhat similar to the local concentration observed in natural systems at the inflammatory site. 37,38 It is important to emphasize that both approaches used herein to mimic the in vivo oxidative environment at the tissue-biomaterial interface have never been applied to study hernia repair meshes.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…It is believed that this in vitro system provides a sufficient correlation with the in vivo oxidative stress. 20,36 The hypochlorite concentration used in this study is somewhat similar to the local concentration observed in natural systems at the inflammatory site. 37,38 It is important to emphasize that both approaches used herein to mimic the in vivo oxidative environment at the tissue-biomaterial interface have never been applied to study hernia repair meshes.…”
Section: Discussionsupporting
confidence: 59%
“…In an attempt to simulate the effect of hypochlorite anions produced by MPO, the meshes were treated in a sodium hypochlorite solution with a concentration of 1 m M . It is believed that this in vitro system provides a sufficient correlation with the in vivo oxidative stress . The hypochlorite concentration used in this study is somewhat similar to the local concentration observed in natural systems at the inflammatory site .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Plasma fibrinogen is susceptible to oxidative stress [35], and fibrinogen exposed to reagents present during oxidative stress resulted in decreased fibrin fiber diameter [36].…”
Section: Discussionmentioning
confidence: 99%
“…Anorexia nervosa, associated with high cardiovascular mortality is related to reduced L-arginine transport, NOS activity and cGMP basal levels in platelets due to increased OS [10]. Fibrinogen (Factor X) is one of the plasma proteins most susceptible to oxidative modification, which may cause thrombotic/ bleeding complications associated with many pathophysiological states [11]. Hence, platelet OS and intra-platelet redox control are basic research subjects of relevance for understanding the involvement of platelets in atherogenic, inflammatory and antigenic processes, beyond their crucial role in haemostasis and thrombosis.…”
Section: Introductionmentioning
confidence: 99%